Impact of Digital Marketing, Such As Social Media Marketing, Mobile Marketing and E-Mail Marketing, On Customer Buying - Aziz, Khanda Gharib; Abdulqadir, Sarya Omar; Hama amin, Soma Sabah (REVENUE: Jurnal Manajemen Bisnis Islam, 2023)
Digital marketing is the promotion of a product or buying and selling behavior through electronics and the Internet. From this perspective, this study was conducted to find out the role and impact of each of the three types of digital marketing (social media marketing, email marketing, mobile marketing). The significance of our research is that it enables people to have a clear understanding about digital marketing and how the use of technology and digital marketing changes their buying attitudes. The research was conducted through a survey through the publication of Google forms on several residents of the Kurdistan Region aged 18 to over 50 years and residents of Halabja and Sulaimani and the surrounding areas of Halabja and Sulaimani and surrounding areas. About 250 respondents were recruited which were obtained through an adaptive questionnaire. Conclusion We found that all three types of digital marketing influence customers’ purchases separately, but both types of digital marketing (social media marketing, email marketing) play a role in encouraging people to buy digitally. This will cause the Kurdish people to trust the digital market and gradually replace the traditional market. In conclusion, this study shows that digital marketing has been able to influence customer’s buying behavior and encourage them to do more in this way.